The Brazilian Soil Spectral Library (BSSL): A general view, application and challenges - Demattê, José A.M.; Dotto, André Carnieletto; Paiva, Ariane F.S.; Sato, Marcus V.; Dalmolin, Ricardo S.D.; de Araújo, Maria do Socorro B.; da Silva, Elisângela B.; Nanni, Marcos R.; ten Caten, Alexandre; Noronha, Norberto C.; Lacerda, Marilusa P.C.; de Araújo Filho, José Coelho; et al. (Elsevier, 2019)
The present study was developed in a joint partnership with the Brazilian pedometrics community to standardize and evaluate spectra within the 350–2500 nm range of Brazilian soils. The Brazilian Soil Spectral Library (BSSL) began in 1995, creating a protocol to gather soil samples from different locations in Brazil. The BSSL reached 39,284 soil samples from 65 contributors representing 41 institutions from all 26 states. Through the BSSL spectra database, it was possible to estimate important soil attributes, such as clay, sand, soil organic carbon, cation exchange capacity, pH and base saturation, resulting in differences among the multi-scale models taking Brazil (overall), regional and state scale. In general, spectral descriptive and quantitative behavior indicated important relationship with physical, chemical and mineralogical properties. Statistical analyses showed that six basic patterns of spectral signatures represent the Brazilian soils types and that environmental conditions explain the differences in spectra. This study demonstrates that spectroscopy analyses along with the establishment of soil spectral libraries are a powerful technique for providing information on a national and regional levels. We also developed an interactive online platform showing soil sample locations and their contributors. As soil spectroscopy is considered a fast, simple, accurate and nondestructive analytical procedure, its application may be integrated with wet analysis as an alternative to support the sustainable management of soils.
Keywords: Pedometrics; Proximal sensing; Spectral sensing; Vis-NIR-SWIR spectroscopy